Exploratory cohort study to determine if dry cow vaccination with a Salmonella Newport bacterin can protect dairy calves against oral Salmonella challenge. (27th May 2019) - Foster, Derek; Jacob, Megan; Stowe, Devorah; Smith, Geof
Abstract: Background: Salmonellosis is a major cause of morbidity and mortality in neonatal calves, often occurring before preventative vaccines can be administered. Hypothesis/Objective: To evaluate the protective effect on calves of colostrum from cows vaccinated with a commercially available Salmonella Newport bacterin against a Salmonella Typhimurium challenge. Animals: Twenty Holstein bull calves from a university dairy farm. Methods: Nonrandomized placebo‐controlled trial in which colostrum was harvested from 30 cows that received 2 doses of either Salmonella bacterin or saline before calving. Colostrum collected from each group was pooled and fed to 2 groups of 10 calves at birth. At approximately 2 weeks of age, calves were challenged with Salmonella Typhimurium. Clinical, hematologic, microbiological, and postmortem findings were compared between the 2 groups. Results: No differences in mortality, clinical findings, hematology results, blood and fecal cultures, or necropsy findings between the 2 groups were observed. Vaccinated cows had higher colostral titers, and calves fed this colostrum had higher serum titers (mean difference, 0.429; mean [SE], 0.852 [0.02] for vaccinated versus 0.423 [0.02] for control calves). Conclusions and Clinical Importance: Transfer of colostral immunoglobulins from Salmonella enterica serotype Newport bacterin to neonatal calves was not sufficient to decrease mortality, clinical signs, sepsis, intestinal damage, or fecal shedding when exposed to a highly pathogenic Salmonella isolate. A large‐scale randomized controlled clinical trial is needed to evaluate the efficacy of this bacterin when administered in the dry period for prevention of salmonellosis in neonatal calves.